Mortality in rabbits transported for slaughter - Voslarova, Eva; Vecerek, Vladimir; Bedanova, Iveta; Vecerkova, Lenka (Animal science journal, 2018)
During transport rabbits may be exposed to various stressors which can compromise both their welfare and meat quality. Mortality related to the commercial transport of rabbits for slaughter was analyzed in the Czech Republic in the period from 2009 to 2016. The overall transport-related mortality of rabbits was 0.19%. Transport distance was found to have an impact on rabbit mortality; significantly (p < .001) greater losses were found in rabbits transported over longer distances. Mortality rates ranged from 0.02% in rabbits transported over distances of less than 50 km to 0.29% in rabbits transported over distances exceeding 400 km. A significantly (p < .001) increased risk was also associated with shipments in which 500 and more rabbits were delivered per batch. No effect of season was found. Our results show that rabbits can be transported within a wide range of temperatures (from -5 to 19.9°C) with no negative impact on mortality in transit. However, journeys carried out at temperatures below -5°C and above 20°C were associated with increased death losses (0.17% and 0.15%, respectively).
Keywords: Animal Welfare; Temperature; maso; mortality; kvalita jídla; Mortality; Česká republika; Transportation; doprava; temperature; králíci; rabbit; Czech Republic; Time Factors; Animals; distance; jatka; zvířata; časové faktory; Rabbits; mortalita; Abattoirs; Food Quality; Risk; teplota; Meat; transport; riziko; pohoda zvířat